A three-component Breakfast Quality Score (BQS) to evaluate the nutrient density of breakfast meals - Poinsot, Romane; Maillot, Matthieu; Masset, Gabriel; Drewnowski, Adam (Frontiers in Nutrition, 2023)
Background: Nutrient profiling methods can be applied to individual foods or to composite meals. This paper introduces a new method to assess the nutrient density of breakfast meals.Objective: To develop a new Breakfast Quality Score (BQS), based on the nutrient standards previously published by the International Breakfast Research Initiative (IBRI) consortium.Methods: BQS was composed of three sub-scores derived from weighted arithmetic mean of corresponding nutrients adequacies: a eLIMf sub-score (energy, saturated fat, free sugars, sodium), a PF (protein and fiber) sub-score and a VMn1-14 micronutrient sub-score where n varied from 0 to 14. The effects of assigning different weights to the eLIMf, PF and VMn were explored in four alternative models. The micronutrients were calcium, iron, potassium, magnesium, zinc, vitamin A, thiamin, riboflavin, niacin, vitamin B5, vitamin B6, vitamin B12, vitamin C, and vitamin D. Micronutrient permutations were used to develop alternate VMn1-14 sub-scores. The breakfast database used in this study came from all breakfasts declared as consumed by adults (>18y) in the French dietary survey INCA3. All models were tested with respect to the Nutrient Rich Food index (NRF9.3). BQS sensitivity was tested using three prototype French breakfasts for which improvements were made.Results: Correlations of the models with NRF9.3 improved when the VMn>3 subscore (n>3) was included alongside the PF and eLIMf subscores. The model with (PF+VMn) and eLIMf each accounting for 50% of the total score showed highest correlations with NRF9.3 and was the preferred final score (i.e. BQS). BQS was sensitive to the changing quality of three prototype breakfasts defined as tartine, sandwich and cereal.The proposed BQS was shown to valuably rank the nutritional density of breakfast meals against a set of nutrient recommendations. It includes nutrients to limit along with protein, fiber and a variable number of micronutrients to encourage. The flexible VMn sub-score allows for evaluation of breakfast quality even when nutrient composition data are limited.